The Mistakes of a Public Communication in the Ebola Crisis in Spain - González, Rafael Barberá; Victoria Cuesta (European Journal of Social Science Education and Research, 2019)
This work analyzes the impact of the outbreak of hemorrhagic fever caused by the Ebola virus in Spain in the field of communication. The communication of such a crisis entails an interaction of information between individuals and institutions. Accuracy in the messages that are disseminated is key to the good resolution of the crisis. In this case of the Ebola crisis the impact in the Spanish media was very remarkable not only of the evolution of the crisis but also of the public information that were being made known by the authorities. The errors committed in this public communication, especially in the first institutional appearance, will be analyzed and possible solutions will be provided for future crises. In addition, the information behavior that was given in social networks by the authorities will be analyzed. To perform this work, bibliographical sources, data analysis and the media have been used.
Keywords: crisis - communication - public - ebola – media